Incomplete Recovery of CD4 Cell Count, CD4 Percentage, and CD4/CD8 Ratio in Patients With Human Immunodeficiency Virus Infection and Suppressed Viremia During Long-term Antiretroviral Therapy. (2nd March 2018) - Mutoh, Yoshikazu; Nishijima, Takeshi; Inaba, Yosuke; Tanaka, Noriko; Kikuchi, Yoshimi; Gatanaga, Hiroyuki; Oka, Shinichi
Abstract : Using change point analysis, this study showed that even after long-term successful antiretroviral therapy in human immunodeficiency–infected patients with suppressed viremia, the CD4 cell count, CD4 percentage, and CD4/CD8 ratio did not recover to levels seen in healthy individuals. Abstract: Background: The extent and duration of long-term recovery of CD4 count, CD4 percentage (CD4%), and CD4/CD8 ratio after initiation of combination antiretroviral therapy (cART) in patients with a suppressed viral load (VL) are largely unknown. Methods: Patients infected with human immunodeficiency virus type 1 who started cART between January 2004 and January 2012 and showed persistent viral suppression (VL, <200 copies/mL) for ≥4 years were followed up at the AIDS Clinical Center in Tokyo. Change point analysis was used to determine the time point when CD4 count recovery shows a plateau, and a linear mixed model was applied to estimate the CD4 count at this change point. Results: Data were analyzed from 752 patients (93% male; median age, 38 years; median baseline CD4 cell count, 172/µL [interquartile range CD4%, 13.8%]; CD4/CD8 ratio, 0.23). The median follow-up period was 81.2 months, and 91 patients (12.1%) were followed up for >10 years. Change point analysis showed that CD4 count, CD4%, and CD4/CD8 ratio continued to increase until 78.6, 62.2, and 64.3 months, respectively, with adjusted means of 590/µL (95% confidence interval, 29.5%, and 0.89, respectively, at the change point. Although CD4 counts ≥500/μL were achieved in 73.8% of the study patients, they were not achieved in 48.2% of those with a baseline CD4 count <100/μL. Neither the CD4% nor the CD4/CD8 ratio were normalized in a majority of patients. Conclusions: The results showed lack of normalization of CD4 count, CD4%, and CD4/CD8 ratio to the levels seen in healthy individuals even after long-term successful cART in patients with a suppressed VL.